From disease to noninvasive intracranial monitoring - Folchini, Caroline Mensor; Karuta, Simone Carreiro Vieira; Ricieri, Marinei Campos; Motta, Fábio Araújo; Manços, Guilherme de Rosso; Frigieri, Gustavo; Maeda, Adriano Keirijo (Arquivos de Neuro-Psiquiatria, 2022)
Professor Sérgio Mascarenhas was a Brazilian researcher with a vast legacy. His work paved the way for new research possibilities by consolidating the use of innovation and transdisciplinary science. In Medicine, he proposed changes to what had previously been well-accepted concepts, and his contributions have influenced medical practices. Although many authors consider intracranial pressure (ICP) as an unrivaled variable for monitoring and diagnosis of many diseases, its clinical applicability is still the subject of debate in the literature because of the difficulty in standardizing protocols. Mascarenhas's research and the creation of a device for noninvasive monitoring of intracranial compliance are discussed and are shown to have led to the creation of Brain4care, a start-up, and a new perspective on the debate on ICP monitoring.
Keywords: Hydrocephalus, Normal Pressure; Parkinson Disease; Monitoring